PENGEMBANGAN BUKU SUPLEMEN PENDEKATAN MOLEKULAR TAKSONOMI HEWAN VERTEBRATA - Haqqi Anajili Setyanto; Mohamad Amin; Umie Lestari (Graduate School of Universitas Negeri Malang, 2016)
Textbook is a book that is used to achieve the learning objectives in the learning activities. One type textbook is the supplements book. The supplements book have characteristics not integrated with the learning objectives directly, but the goal is to reinforce the concepts on the learning objectives to be achieved. Supplement books developed using the book contains a molecular approach to subjects Vertebrate Animal Taxonomy with Borg and Gall development model. The book supplements validated by subject matter experts, development specialists, and tested individually at 12 students. Material validation results demonstrate the value of 90.53%, 87.63% validation of the development of the book, and test results readability 85.06%. Overall the book is developed in the category of valid and good.Buku ajar merupakan buku yang digunakan untuk mencapai tujuan pembelajaran dalam kegiatan pembelajaran. Salah satu jenis buku ajar adalah buku suplemen. Buku suplemen memiliki karakteristik tidak terintegrasi dengan tujuan pembelajaran secara langsung, namun memiliki tujuan untuk memperkuat konsep-konsep pada tujuan pembelajaran yang ingin dicapai. Buku suplemen yang dikembangkan menggunakan merupakan buku berisi pendekatan molekular untuk matakuliah Taksonomi Hewan Vertebrata dengan model pengembangan Borg and Gall. Buku suplemen divalidasi oleh ahli materi, ahli pengembangan, dan diuji coba perorangan pada 12 mahasiswa. Hasil validasi materi menunjukkan nilai 90,53%, validasi pengembangan buku 87,63%, dan hasil uji keterbacaan 85,06%. Secara keseluruhan buku yang dikembangkan dalam kategori valid dan baik.